Defining the in vivo characteristics of acute myeloid leukemia cells behavior by intravital imaging. Issue 2 (13th December 2018) - Duarte, Delfim; Amarteifio, Saoirse; Ang, Heather; Kong, Isabella Y; Ruivo, Nicola; Pruessner, Gunnar; Hawkins, Edwin D; Lo Celso, Cristina
Abstract: The majority of acute myeloid leukemia (AML) patients have a poor response to conventional chemotherapy. The survival of chemoresistant cells is thought to depend on leukemia‐bone marrow (BM) microenvironment interactions, which are not well understood. The CXCL12/CXCR4 axis has been proposed to support AML growth but was not studied at the single AML cell level. We recently showed that T‐cell acute lymphoblastic leukemia (T‐ALL) cells are highly motile in the BM; however, the characteristics of AML cell migration within the BM remain undefined. Here, we characterize the in vivo migratory behavior of AML cells and their response to chemotherapy and CXCR4 antagonism, using high‐resolution 2‐photon and confocal intravital microscopy of mouse calvarium BM and the well‐established MLL‐AF9‐driven AML mouse model. We used the Notch1‐driven T‐ALL model as a benchmark comparison and AMD3100 for CXCR4 antagonism experiments. We show that AML cells are migratory, and in contrast with T‐ALL, chemoresistant AML cells become less motile. Moreover, and in contrast with T‐ALL, the in vivo exploratory behavior of expanding and chemoresistant AML cells is unaffected by AMD3100. These results expand our understanding of AML cells‐BM microenvironment interactions, highlighting unique traits of leukemia of different lineages. Abstract : Using intravital imaging, we show that cell motility is a characteristic feature of both acute myeloid leukemia (AML) and T‐cell acute lymphoblastic leukemia (T‐ALL). However, in contrast to T‐ALL, chemoresistant AML cells are less migratory. Furthermore, CXCR4 regulates bone marrow (BM) retention of both leukemias, but is redundant in fine‐tuning leukemia‐supporting interactions between parenchymal AML cells and the BM microenvironment. In contrast, T‐ALL cells depend on CXCR4 to interact with and survive within the BM parenchyma.